Strategic Choice of Doctoral Education and Dynamic Managerial Capabilities in Supporting Executives Performance: An Exploratory Study - Irawan, Dadang; Supratikno, Hendrawan; Hariandja, Evo; Parani, Rizaldi (International Journal of Innovative Research and Scientific Studies, 2025)
Improving human capital through education is considered an investment decision. In Indonesia, the interest of non-academics in pursuing doctoral programs is increasingly widespread. The purpose of this study is to explore the dynamics of strategic choices in doctoral education and dynamic managerial capabilities on executive performance. The data analysis process includes a crucial stage of data coding, following Yin's approach for case studies as the research method of this study. By employing unstructured techniques with five executives, it gathered the unique insights of each participant, enabling a deeper understanding of the phenomenon. The conceptual framework of the results of the study shows the findings of conditions where dynamic managerial capabilities support executive performance and the interaction of dynamic managerial capabilities and strategic choices in doctoral education supports executive performance. The strategic choice of doctoral education supports executive performance for two informants. Instead, three informants do not support it directly because external conditions require time to be overcome or because of the motive for doctoral education itself. The practical implication provides insight into the diverse motives and levels of relevance of educational programs that provide managerial capabilities to adapt to dynamic business practices.